The effect of welding direction in the fatigue life of aluminium FS welded lap joints. Issue 6 (7th December 2015) - Duarte, F.F.; Infante, Virgínia Isabel V.; Moreira, P.M.G.; de Freitas, M.; de Castro, P.M.S.T.
Abstract : Purpose: – Friction stir welding lap joints of aluminum alloy AA6082-T6 were joined using two distinct configurations. The purpose of this paper is to study the effect of the welding line direction on the fatigue life of the specimens. For that purpose, specimens with the welding line parallel to the loading direction and with the welding line perpendicular to the loading direction were designed and manufactured. Fatigue tests were performed under constant amplitude load and stress ratio of R =0.1. As shown in previous studies, the hook defect plays a decisive role in the mechanical behavior of the joint, in particular when submitted to fatigue. The specimen geometry with the welding line parallel to the loading direction showed a superior fatigue behavior: for a given number of cycles to rupture, the level of stress is approximately twice as high as for the perpendicular configuration. Design/methodology/approach: – Two finite element models were created in order to study the behavior of the welded zone and, in particular, to compare influence of the hook defect in both configurations. Findings: – The specimen geometry with the welding line parallel to the loading direction showed a superior fatigue behavior: for a given number of cycles to rupture, the level of stress is approximately twice as high as for the perpendicular configuration. Originality/value: – The main objective of this work is to study the effect of the welding line direction on the fatigue life of the specimens. For that purpose, specimens with the welding line parallel to the loading direction and with the welding line perpendicular to the loading direction were designed and manufactured. Fatigue tests were performed under constant amplitude load and stress ratio of R =0.1. As shown in previous studies, the hook defect plays a decisive role in the mechanical behavior of the joint, in particular when submitted to fatigue.